The Relationship Between Strategic Types and Strategic Management Processes - Ghaleb, Belal Dahiam Saif (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the definition of strategic management processes, their stages, and how different strategy types are integrated within these processes. It examines how strategies align with organizational objectives, environments, and performance. The aim is to enhance knowledge and understanding to improve strategic decision-making and ensure effective strategic planning and implementation. Using a compilation and analysis method, this study synthesizes previous research to help businesses gain competitive advantage, adapt to changing conditions, and assess performance. The study focuses on the relationships between strategy types and strategic management processes, as well as the potential future impacts of these interactions.